Combination therapy for severe diffuse alveolar hemorrhage accompanied with untreated systemic lupus erythematosus in a child: a case report. Issue 2 (3rd July 2017) - Sato, Tomomi; Nakatsuji, Eri; Shimizu, Junji; Masuda, Toshiki; Okuda, Yusuke; Sakai, Tomoyuki; Sawai, Toshihiro; Maruo, Yoshihiro
Abstract: Background: Diffuse alveolar hemorrhage is considered a rare and acute complication of systemic lupus erythematosus, which occurs even if the patient had been treated with appropriate lupus therapy. Despite high mortality, a therapy for diffuse alveolar hemorrhage has not been established yet. Herein, we report a case of systemic lupus erythematosus in a young girl with diffuse alveolar hemorrhage who previously refused the standard therapy of lupus. She presented in an extremely serious condition; however, a combination therapy with plasmapheresis, steroid pulse therapy, and cyclophosphamide pulse therapy was successful in treating her. Case presentation: A 14-year-old girl with systemic lupus erythematosus, whose parents refused administration of the appropriate treatment was admitted to our hospital by ambulance at 7 months after diagnosis of SLE. She presented with fever, cough, hemosputum, dyspnea and sudden consciousness disorder. Using computed tomography and bronchoscopy, she was diagnosed with diffuse alveolar hemorrhage. Immediately, mechanical ventilation and a combination therapy of plasmapheresis, steroid pulse therapy and cyclophosphamide pulse therapy was initiated. One month after admission, her respirator was withdrawn. She recovered with no sequelae, and she along with her parents accepted the standard therapy for SLE. Conclusions: Previous reports have mentioned the mortality rate of diffuse alveolar hemorrhage to be 42.1% with no differences between children and adults. Hence, a standard therapy needs to be established with the goal of improving the survival rate of this condition.